Planning procedures towards high climatic quality cities. Example referring to Lisbon - Maria João Alcoforado (Finisterra - Revista Portuguesa de Geografia, 2006)
The different stages of research on high climatic quality city are presented in this paper: acquisition of appropriate urban climate information, analysis of different urban climate features and selection of planning strategies (accordingly with the climate zone). Then, with the aid of a GIS, systematic guidelines for planning can be given. As a result, different types of benefits for city dwellers are to be expected (comfort, health, economic). Lisbon is presented as a case study. It is shown how the “translation” of the knowledge of Lisbon’s urban climate into simple guidelines for urban planning in order to mitigate the urban heat island, promote ventilation and increase air quality, was carried out. To this end, maps of the physical features of the city of Lisbon were drawn, synthesised into “urban homogeneous units” map. Climate guidelines are specified for each of the six groups of units (brought together according to urban morphology, topography and position in town.